Cultural landscapes for water management. A research work plan - Basso S. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
Dry-stone walls and terraces are typical features of the Mediterranean landscape. Traditional knowledge suggests they might have been constructed to satisfy agricultural water requirements. However, only few studies have tried to quantify their effects on soil moisture in agricultural fields, suggesting deteriorating conditions when maintenance is lacking. This is the case of the Mediterranean region, as a consequence of changes of the social and economic systems. The research work plan outlined here aims to improve scientific understanding of the functioning of terraces and dry-stone walls and quantify their potential for water harvesting and management. In particular, the following aspects will be investigated: (i) modifications of stocks and volatility of soil moisture due to terracing, and its effect on catchment-scale water partitioning; (ii) water yields and water-saving performance of dry-stone walls, and their contribution to water budgets in semi-arid regions; (iii) design innovation required to cope with changes of the climate (e.g., building features, distance among structures); (iv) economic value of services (e.g., water harvesting and hazard mitigation) provided by terraces and dry-stone walls and ways to establish payments for these services. Findings of this project will lay the foundation for a large scale restoration of cultural landscapes aimed at counteracting water scarcity and buffering the effect of climate change in the Mediterranean basin.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)